Evaluation of lattice dynamics, infrared optical properties and visible emissions of hexagonal GeO2 films prepared by liquid phase deposition. Issue 48 (4th December 2017) - Sun, Yabin; Xu, Weili; Fu, Xiaohong; Sun, Zihan; Wang, Junyong; Zhang, Jinzhong; Rosenbach, Daniel; Qi, Ruijuan; Jiang, Kai; Jing, Chengbin; Hu, Zhigao; Ma, Xueming; et al.
Abstract : GeO2 films with thicknesses from 10 to 22 μm have been deposited on polished Si(100) substrates using liquid phase deposition. Abstract : GeO2 films with thicknesses from 10 to 22 μm have been deposited on polished Si(100) substrates using liquid phase deposition. The effects of deposition time on the thickness, crystallographic and vibrational properties, as well as optical characteristics have been investigated by X-ray diffraction (XRD), scanning electron microscopy, Raman scattering and infrared (IR) reflectance/transmittance. The XRD analysis indicates the presence of the pure hexagonal GeO2 phase, and the space group P 31 21, in the films, which is confirmed by the frequencies and intensities of the Raman- and IR-active phonon modes. Furthermore, the optical constants n and k in the mid- and far-IR regions for the α-GeO2 films have been extracted using IR variable angle spectroscopic ellipsometry. Interestingly, we observe that the refractive index n in certain mid- and far-IR regions is below unity ( n < 1), which explains the abnormal phenomena observed in the IR transmittance spectra. Based on this unique characteristic, the GeO2 films can be used as attenuated total reflection mid- and far-infrared hollow waveguides for infrared waves. In addition, the photoluminescence spectra were collected in the visible range to investigate the related defects in the GeO2 films. The emission band near 2.1 eV originates from the X3 Ge–GeX2 related defects, while the bands located at around 2.4 and 2.8 eV are related to the Ge–O related defects, which are dominant in the as-deposited GeO2 films. These findings provide further information for developing GeO2 -based optical devices.